Characterization of the transverse relaxation rates in lipid bilayers. - Watnick, P I (1990)
The 2H NMR transverse relaxation rates of a deuterated phospholipid bilayer reflect slow motions in the bilayer membrane. A study of dimyristoyl lecithin specifically deuterated at several positions of the hydrocarbon chains indicates that these motions are cooperative and are confined to the hydrocarbon chains of the lipid bilayer. However, lipid head group interactions do play an important role in modulating the properties of the cooperative fluctuations of the hydrocarbon chains (director fluctuations), as evidenced by the effects of various lipid additives on the 2H NMR transverse relaxation rates of the dimyristoyl lecithin bilayer.